Betraying a generation how education is failing young people - Ainley, Patrick (Policy Press, 2023)
From primary to post-graduate schools Patrick Ainley explains how English education is now driven by the economy and politics. Addressed to teachers and students at all levels of learning, it concludes by suggesting how we can begin to contribute towards a more meaningful and productive society
Previously issued in print: 2016. - Includes bibliographical references and index
Keywords: Educational sociology / Great Britain; Education and state; Education / Aims and objectives; Social mobility; Labor supply / Effect of education on / Great Britain